THE DECISION TO INVADE: AN INTERNAL PERSPECTIVE TO THE RUSSIAN INVASION OF UKRAINE - Shafy Ramadhan, Muhammad Damar (UI Scholars Hub, 2023)
The invasion of Ukraine by Russia marked a new turning point in the history of the 21st century and has had far-reaching effects for much of the globalized world. The intensity of such an unexpected and unprovoked war has made it crucial to seek out the reasons why Russia decided to wage war on Ukraine. As such, there is a need to look for a deeper origin of the conflict, especially the unique circumstances that led to such policy being pursued. A comprehensive and theoretical approach that connects all the dots into one chronological picture is required. To that end, this research attempts to analyze the war in Ukraine and explore the root causes of why Russia decided to invade, primarily through its internal perspective and the intervening variables that made it happen. It may serve as a reminder of how the compounding effects of a nation’s traumatic past, the corruption of power by its elites, the pacification of its civil society, and the hubris of its leaders, could lead to a disastrous and unforeseen outcome.